ANALISIS PERBEDAAN PELAPORAN CSR PADA BUMN DAN BUMS YANG TERDAFTAR DI BEI TAHUN 2014 - Heny Sidanti; Alfian Syaikhori (Universitas PGRI Madiun, 2017)
The purpose of this study was to analyze the empirical evidence of differences in reporting Corporate Social Responsibility (CSR) in state-owned enterprises and private enterprises listed on the Stock Exchange in 2014. This research is a quantitative research. The study population was BUMN and BUMS listed in the Indonesia Stock Exchange (BEI). Samples are 22 companies consisting of 12 BUMN companies and 10 companies BUMS listed in the Indonesia Stock Exchange (BEI). The analysis technique used using independent samples t-test. The results showed that there was no significant difference between Corporate Social Responsibility (CSR) of the company's state-owned enterprises with private enterprises in terms of economic sectors. A description of the analysis showed that CSR BUMN in sectors of the economy is greater than the company BUMS, but the differences were considered less significant. There were no significant differences between the Corporate Social Responsibility (CSR) of the company's state-owned enterprises with private enterprises in terms of the environmental sector. A description of the analysis showed that CSR state-owned companies in the environmental sector is greater than the company BUMS, but the differences were considered less significant. There are significant differences between the Corporate Social Responsibility (CSR) of the company's state-owned enterprises with private enterprises in terms of the employment sector. A description of the analysis showed that CSR state-owned enterprises in the employment sector is greater than the company BUMS, and the difference is considered to be very significant CSR.Keywords : BUMN , BUMS, CSR